PENGARUH KONTRIBUSI PAJAK RESTORAN, PAJAK HIBURAN, PAJAK HOTEL, DAN PAJAK PENERANGAN JALAN TERHADAP PENDAPATAN ASLI DAERAH DI KOTA CIMAHI - Vera Amelia; Jouzar Farouq Ishak (Faculty of Economics and Business, Universitas Warmadewa, 2023)
The purpose of this study was to understand how the contribution of restaurant tax, entertainment tax, hotel tax, and street lighting tax to PAD revenue in Cimahi City from 2016-2020, simultaneously and partially. The method used is quantitative through a descriptive approach to secondary data, namely the Cimahi City Regional Revenue Revenue Report from 2016-2020 which is carried out with IBM SPSS Statistics Version 25.0. The sample in this study is 60 months. The results of this study prove that the restaurant tax, entertainment tax, hotel tax, and street lighting tax individually or collectively have no significant effect on PAD in Cimahi City.